TI_GERICHTE 12.2023.138 vom 5. März 2024 , Compravendita immobiliare - responsabilità per difetti - notifica dei difetti - TI Tribunale d'appello (2024)
Compravendita immobiliare - responsabilità per difetti - notifica dei difetti